A Novel Approach to Design Chitosan-Polyester Materials for Biomedical Applications - Tatiana A. Akopova; Tatiana S. Demina; Alexander N. Shchegolikhin; Tikhon S. Kurkin; Christian Grandfils; Nikolay S. Perov; Alexander S. Kechekyan; Alexander N. Zelenetskii (International Journal of Polymer Science)
A novel approach to design chitosan-polyester materials is reported. The method is based on mechanical activation and effective intermixing of the substrates under high pressure and shear deformation in the course of solid-state reactive blending. The marked departure of this approach from previous practice resides on exploitation of a variety of chemical transformations of the solid polymers that become feasible under conditions of plastic flow. Low temperatures (above Tg but below the melting points of the crystalline polymers) are maintained throughout the process, minimizing mechanical and oxidative degradation of the polymers. Morphology as well as structural, mechanical, and relaxation properties of those prepared blends of chitosan with semicrystalline poly(L,L-lactide) and amorphous poly(D,L-lactide-co-glycolide) has been studied. Grafting of polyester moieties onto chitosan chains was found to occur under employed pressures and shear stresses. The prepared polymer blends have demonstrated an amphiphilic behavior with a propensity to disperse in organic solvents that widens possibilities to transform them into promising materials for various biomedical applications.